Determination of tumour dose response threshold and implication on survival in patients with HCC treated with Y90 radiation segmentectomy: a simple semi-quantitative analysis. Issue 8 (30th March 2021) - Cheng, Bernard; Sethi, Ila; Villalobos, Alex; Wagstaff, William; Schuster, David M.; Bercu, Zachary; Brandon, David; Kokabi, Nima
Abstract : Purpose: To evaluate the relationship between Yttrium-90 (Y90) tumour dose and response rate in patients with hepatocellular carcinoma (HCC) who undergo Y90 radiation segmentectomy (Y90-RS) and to determine implication on overall survival (OS). Materials and methods: Post Y90-RS Bremsstrahlung single-photon emission computed tomography/CT of 105 HCC patients with 110 treatments performed with glass microspheres was retrospectively analysed. The dose-volume histogram of the targeted tumour was determined with commercially available dosimetry software. Tumour response at 3 months was evaluated using modified Response Evaluation Criteria in Solid Tumours. Tumour dose thresholds associated with the objective response with 80% specificity were then used to evaluate implication on OS using Kaplan–Meier estimation and log-rank analysis. Results: Tumour dose thresholds to predict objective response with 80% specificity were the following: maximum tumour dose (748 Gy), mean tumour dose (568 Gy), minimum tumour dose of 30% tumour volume (608 Gy), minimum tumour dose of 50% tumour volume (565 Gy), minimum tumour dose of 70% tumour volume (464 Gy) and minimum tumour dose of 100% tumour volume (213 Gy). These parameters all significantly predicted tumour response with areas under the ROC curve of >0.6. Mean tumour dose of ≥250 Gy predicted median OS of 43.67 vs. 17.87 months for others ( P = 0.026). Minimum dose ≥180 Gy to 100% of tumour volume predicted median OS of 44.93 vs. 35.87 months for others ( P = 0.043). Conclusion: In patients with HCC undergoing Y90-RS, mean tumour dose ≥250 Gy and minimum tumour dose of ≥180 Gy to 100% of tumour volume are both significantly correlated with higher objective tumour response and prolonged survival.